Practical Use of Damage Functions for Environmental Preventive Conservation and Sustainability—Examples from Naturally Ventilated Buildings - David Thickett (Heritage, 2023)
This work explores the potential of using damage functions to assess cultural heritage environments. Changes caused by dimensional variation due to fluctuations in relative humidity are assessed using two accessible functions, and a third is discussed. The risk of mould growth is assessed from a time series of temperature and RH data. The results of previous studies comparing predictions from four functions to observed mould formation are reviewed, and the practical aspects of using the functions are described. Two situations related to metal and stone risk are described, comparing environments for display and assessing new or refitted buildings for storage. The use of functions to improve sustainability and their combination with performance models to predict carbon footprints are discussed.